Acoustically stimulated phase transition and low temperature optical spectra in PbI₂ crystal - Bilyi, M.M.; Gorban, I.S.; Dmitruk, I.M.; Salivonov, I.M.; Ostrovskii, I.V. (Физика низких температур, 1998)
The influence of intensive ultrasonic wave on the crystal structure of PbI₂ was investigated. Acoustically stimulated phase transition have been observed for the first time.